2009
DOI: 10.3200/jach.57.4.471-480
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Climate for Overweight and Obese Students in a Student Health Setting

Abstract: The authors make recommendations for improving the health care climate for overweight and obese students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Physician weight counseling is associated with increases in patient desire and attempts to lose weight, 46,47 yet as few as 28.9% of physicians inform obese patients of their BMI category, and even fewer provide weight-related counseling. 48 Given that health providers report feelings of discomfort as a barrier to discussing weight with patients, 49 the current findings offer specific suggestions for providers of preferred, motivating weight terminology that can facilitate patient-provider discussions. Although the present findings were primarily consistent across socio-demographic characteristics, it is also important to recognize variability in patient preferences.…”
Section: Discussionmentioning
confidence: 93%
“…Physician weight counseling is associated with increases in patient desire and attempts to lose weight, 46,47 yet as few as 28.9% of physicians inform obese patients of their BMI category, and even fewer provide weight-related counseling. 48 Given that health providers report feelings of discomfort as a barrier to discussing weight with patients, 49 the current findings offer specific suggestions for providers of preferred, motivating weight terminology that can facilitate patient-provider discussions. Although the present findings were primarily consistent across socio-demographic characteristics, it is also important to recognize variability in patient preferences.…”
Section: Discussionmentioning
confidence: 93%
“…Correspondingly, the stigmatisation associated with overweight and obesity (Bissell, Peacock, Blackburn, & Smith, 2016;Lupton, 2013) was taken seriously by most GPs in this study. While a related cautiousness in approaching the topic of overweight can be seen to hinder conversations between primary health care physicians and patients (Hansson et al, 2011;Michie, 2007;Pedersen & Ketcham, 2009), most of the GPs in this study prioritised the creation of safe, inclusive environments for patients. The focus for these practitioners was on the contexts and needs of their individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…This concurs with research (Peters et al, 2013;Puhl & Brownell, 2001) finding that GPs' low self-efficacy and doubt in their ability to "treat" overweight and obesity are key obstacles to engaging patients in discussions about weight. Other studies have also found that GPs avoid discussions about overweight with their patients because of a concern that such discussions may cause offence and/or provoke a negative reaction (Hansson, Rasmussen, & Ahlstrom, 2011;Michie, 2007;Pedersen & Ketcham, 2009).…”
mentioning
confidence: 99%
“…Implementing stigma reduction efforts during medical training may help prevent and attenuate weight biases that may otherwise remain and potentially worsen in the absence of intervention. The limited work that has documented weight bias among students in medical disciplines suggests that students hold similar biases as health providers , including qualitative research showing that medical students feel that it is socially acceptable to make fun of patients with obesity . Most recently, one study found that 33% of medical students self‐reported moderate to strong explicit weight bias, and 39% exhibited implicit obesity bias, most of whom (67%) were unaware of their negative attitudes .…”
Section: Introductionmentioning
confidence: 99%